From the State of the Khilafah to the Nation State: The Transformation of Islamic Legal Politics - Munir, Muhammad (Islamic Studies, 2017)
This work examines the transformation from the one Muslim state with one khalifah (caliph) to the nation state under Islamic law. It examines the status quo of multiplicity of Muslim states from the perspective of classical Muslim scholars to find out that the transformation from one caliph to dozens of heads in separate Muslim states is not averse to the opinions of top experts of Islamic law even in early Islam. How is the imam (head of state) appointed under Islamic legal discourse and whether the existence of different Muslim states with their own imam violate the cardinal principle of ‘one caliph rule’ of the Shariah. According to Imam Juwayni, it is possible to appoint two or more imam for one Muslim state either to avoid fitnah or if it is difficult for one imam to serve Muslims of far off places or islands. There are four different methods of appointing an imam according to Shah Wali Allah Dihlavi. Dihlavi has based these methods on the way the four successors of the Prophet Muhammad (peace be on him) had been chosen. Efforts for the one caliph rule must be abandoned as it is not practicable today to have one caliph for the whole Muslim world. The paper further asks whether shura and democracy are compatible. Islamist thinkers have differed on this issue. Finally, Islamist thinkers and others have yet to come up with the blue print of a model shura system.